One Motif from "The Man in the Panther's Skin" in the Poem "Several Pictures or Episodes from the Life of a Robber" - Kote Lomidze (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2023)
The article discusses the reception of Shota Rustaveli’s "The Man in the Panther's Skin" in Ilia Chavchavadze’s poem Several Pictures or Episodes from the Life of a Robber (Kako the Robber). The main objective of the article is to highlight the textual and conceptual parallels that connect the scene of Kako and Zakara's meeting with the episodes of the befriending of Rustaveli's heroes. Based on textual parallels, it is substantiated that, regarding the characters' relationship, Ilia Chavchavadze relies on the motif of "liking" found in The Man in the Panther's Skin, according to which the basis of friendship is an external impression and an immediate sensation of social or spiritual kinship. The paper demonstrates that the trust existing between Ilia’s heroes (considered psychologically unconvincing by some researchers) must be dictated by the Rustavelian tradition Based on lexical analysis, it is concluded that the meeting between Kako and Zakara represents an artistic analogue to the befriending scenes of Tariel and Pridon, and Avtandil and Pridon.